Роль дендритных клеток в поддержании структурного гомеостаза кожи - Алиева, Е. Г.; Сулаева, О. Н.; Aliyeva, E. G.; Sulaieva, O. N.; Алієва, Олена Геннадіївна; Сулаєва, Оксана Миколаївна (My University, 2016)
Investigation of mechanisms that determine structural and immunological homeostasis under physiological conditions, alteration of neurohumoral and metabolic control, allows to pose that dendritic cells are the most important modulators of skin structure. This view is focused on current data about classification, molecular hallmarks, mechanisms and effects of their participation in skin structural homeostasis maintaining. As the most powerful and professional antigenpresenting cells, dendritic cells play a crucial role in innate and adaptive immunity, as well as in switching between immunity and tolerance depending on their activation and maturation states. Cutaneous dendritic cells represent a wide spectrum of phenotypically and functionally different subtypes of cells. They are diverse in terms of origin, structure, expression of receptors and co-stimulatory molecules. According to current data, dendritic cells of the skin are classified into several types, including Langerhans cells that express Langerin, CD1a, E-cadherin, etc. In addition, there are several types of dermal dendritic cells. The most numerous are CD11b+ cells that represent about 65% of dermal dendritic cells. In addition there are Langerin+ dermal dendritic cells that demonstrate high XCR1 and lack of EpCam and Sirp1α expression. A few number of dermal DC are cells that express neither Langerin, no XCR1. They have low expression of CD11b and Sirpα, but positive in CX3CR1. In addition to conventional subsets, there is a separate group of plasmacytoid dendritic cells that enter skin under inflammation. This type of cells expresses CD123, CD45RA, CD303 (BDCA2). Authors highlight the functional differences and plasticity of skin dendritic cells populations, and discuss the role of dendritic cells in immune reactions, determination of polarity of immune response, tolerance to antigen and neo-antigens, impact of photoaging and skin aging. Глибоке і багатогранне вивчення механізмів підтримки структурного та імунологічного гомеостазу шкіри в нормі, при зміні нейрогуморального контролю, метаболічних порушеннях і різних варіантах патології шкіри, дозволяють стверджувати, що дендритні клітини є найважливішими модераторами стану шкіри. У даному огляді наведені сучасні дані про класифікацію, молекулярні маркерах і механізми участі дендритних клітин в підтримці структурного гомеостазу шкіри. Крім того, автори розглядають участь дендритних клітин в реалізації реакції імунної системи на пошкодження, поляризації імунної відповіді, толерантності до антигенів, механізмах фото ушкодження та старіння шкіри.
Role of dendritic cells in maintenance of the skin structural homeostasis.
Роль дендритних клітин у підтриманні структурного гомеостазу шкіри
Keywords: skin; Langerhans cells; dermal dendritic cells; immunity; tolerance; шкіра; клітини Лангерганса; дермальні дендритні клітини